Algal-based membrane bioreactors for effective removal of hazardous and toxic contaminants: A comprehensive review - Soumitra Nath; Ashim Das Astapati; Aniket Naha; Indu Sharma; Maulin P. Shah (Current Research in Biotechnology, 2024)
In present times, there is increasing potential of algal-based membrane bioreactors (MBRs) considering the removal of hazardous and toxic contaminants from different wastewater sources. The article summarizes on various types of contaminants that can be effectively removed using algal-based MBRs, including heavy metals and emerging contaminants. The selection criteria, advantages and limitations of different algal species used in algal-based MBRs are also discussed. For optimal performance of algal-based MBRs, operating parameters viz. hydraulic retention time, organic loading rate, nutrient levels, light intensity and duration are essential. The review further highlights the efficient removal of hazardous and toxic contaminants, biomass productivity, and membrane fouling as critical performance indicators. Various applications of algal-based MBRs, particularly in the treatment of municipal and industrial discharges, landfill leachate treatment, and bioremediation of contaminated sites, are also discussed. Finally, the current review identifies the technological limitations, scale-up challenges, and economic feasibility of algal-based MBRs and provides directions of future researches. On the whole, algal-based MBRs offer a sustainable and worthwhile solution in the eradication of harmful and lethal contaminants from various effluent sources.